History of the Singapore Legal System - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2015)
This chapter tells the history of the Singapore legal system, starting with the pre-independence years from the founding of Singapore in 1819. The focus is with the post-independence years, when a new, independent Singapore had to grapple with the consolidation of an equally new legal system.